Ocean Vertical and Deep-Sea Transport: Marine Climatic and Environmental Ecological Effects - QI Qinghua (Haiyang Kaifa yu guanli)
Ocean vertical and deep-sea transports sever as dominant pathways for the interaction between climate environment and deep oceans, and essential channel mechanisms for the deposition, storage, transport of land, atmosphere and surface ocean material and energy into and release from the deep sea, which profoundly shape the full depth marine environmental ecology and the process of global climatic and environmental changes. Focusing on the upper ocean ventilation process, the vertical diapycnal mixing of the intermediate and deep oceans, and the abyssal and benthic ocean transport, this paper summarizes the vertical transport of the ocean and the deep sea transport, and also evaluates their impactions on the ocean climate and environmental ecology. Then research suggestions on the current research status and limitations were put forward. The results show that ocean vertical and deep-sea transports exert critical feedback to and far-reaching influence on climate and environmental change, and act as fundamental drivers for the evolution of ocean climate and environmental ecology in interregional sea area, different oceanic regions and interoceans. It is suggested to enhance the independent research and development of deep levels ocean observation instruments, promote the international cooperation mechanism, strengthen the heterogeneous collaborative network observation capability, deepen the interdisciplinary integration and intersection, enrich the theoretical methods and application practices of full depth ocean mixing and exchange and the interaction of sea-land-air, and effectively improve the comprehensive assessment of the risk induced by ocean thermodynamic and ecological disasters as well as the governance capacity of climate change, with providing strong scientific and technological support for the environmental safety guarantee of high-quality marine development and ecological civilization construction.